High‐precision calibration of MRS thermometry using validated temperature standards: effects of ionic strength and protein content on the calibration. (7th September 2012) - Vescovo, E.; Levick, A.; Childs, C.; Machin, G.; Zhao, S.; Williams, S. R.
Abstract : Currently, there is very limited ability to measure the temperature of the brain, but a direct technique for its estimation in vivo could improve the detection of patients at risk of temperature‐related brain damage, help in the diagnosis of stroke and tumour, and provide useful information on the mechanisms of thermoregulation of the brain. In this article, new calibrations in vitro of MRS thermometry using temperature‐stabilised reference phantoms are reported. The phantoms comprise two concentric glass spheres: the inner sphere contains the phantom material to be measured by MRS, and the outer sphere contains a substance with a known temperature stable to within 0.2 °C. The substances were freezing organic fixed‐point compounds (diphenyl ether and ethylene carbonate, freezing at 26.3 and 35.8 °C, respectively) or temperature‐controlled circulating water. The phantom temperature was continuously monitored with a fluoroptic probe calibrated at the National Physical Laboratory with traceability to the International Temperature Scale 1990 (ITS‐90). The MRS temperature calibration was obtained by measuring the chemical shift of water relative to N ‐acetylaspartate (NAA) in a single voxel as a function of temperature using a 1.5‐T Philips Intera scanner. Measurements were made for several phantom materials to assess the effect of tissue composition on the water–NAA chemical shift against temperature calibration. The phantom mixtures contained 25 mm of NAA buffered to pH 6.5 or 7.5 and several ionic salts or bovine serum albumin (BSA). Spectra were acquired from 25 to 45 °C. The correlation between frequency differences and phantom temperature was very linear with small residuals. However, the linear fitting parameters varied with ionic composition and BSA concentration. The 'apparent' temperature (calibrated using the water–NAA frequency differences) decreased by approximately 1 °C for every 100 mm increase in ionic concentration and increased proportionally to the concentration of BSA. Copyright © 2012 John Wiley & Sons, Ltd. Abstract : New calibrations in vitro of MRS thermometry using temperature‐stabilised reference phantoms are reported. The calibration is sensitive to both ionic strength and protein content of the phantom. The calibration curve used for MRS measurements in vivo should be for a material that closely matches the composition of the tissue; the calibration is sensitive to the different water contents of grey and white matter and to the different ionic milieu of neuronal and glial cells.